Cost Analysis of Ciputat Residence - Sari, Nacita Pramesty; Aliludin, Arson (Journal of Business and Management, 2013)
This research is made to know the cooperation between landowner and developer to build a residence and to know the system of profit-sharing because for this case, the land is owned by the landowner. The method that used for this research is cost analysis. This research used the data from PT. Promacomm.Landowner and developer made an agreement for the profit-sharing. According to the agreement, landowner will get 35% from revenue of the residence. After the calculation, landowner gets only 22% from revenue. But the developer Final project will discuss all the costs that will be incurred by the developer to build a residence. Scope for the final project is discussed about cost analysis for this project and patterns of cooperation between developer and landowner. The assumption is that all units from this residence were soldout in 2 years, with positive NPV and IRR calculations and according to Indonesia's economy is considered stable with inflation at 12%. Inflation is 12% derived from seeing how much the price of raw materials for the property will increase. This paper analysis costs that incurred from developer to developed a residenceÂ Keywords: cooperation system, developer company; PT. Promacomm: Ciputat ResidenceCategory: Finance;